2019
DOI: 10.1016/j.eurox.2019.100064
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of recurrent preterm delivery in asymptomatic women- an anxiety reducing measure?

Abstract: ObjectivesThe QUiPP application is used to predict the risk of recurrent preterm birth (PTB) in asymptomatic high risk women with a previous PTB. Our study aims to evaluate the impact of the use of the QUiPP app on maternal anxiety levels.Study designA retrospective cohort study on asymptomatic pregnant women attending the Prevention of Preterm Birth Clinic in a busy tertiary unit. Women included in the study had a history of previous PTB. The study assessment occurred at approximately 4 weeks prior to the ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Consistent with previous study [5], our study demonstrated that pregnancies with a copper IUD in situ were associated with preterm delivery, which was more than twice as the worldwide preterm livebirths (11.1%) [14]. In our study, preterm premature rupture of membranes (PPROM) had contributed 82.35% of preterm birth in the women with a copper IUD in situ.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous study [5], our study demonstrated that pregnancies with a copper IUD in situ were associated with preterm delivery, which was more than twice as the worldwide preterm livebirths (11.1%) [14]. In our study, preterm premature rupture of membranes (PPROM) had contributed 82.35% of preterm birth in the women with a copper IUD in situ.…”
Section: Discussionsupporting
confidence: 91%